Pengaruh Ukuran Perusahaan, Profitabilitas, Leverage Operasi Dan Net Profit Margin Terhadap Tindakan Perataan Laba (Income Smoothing) Pada Perusahaan Food And Beverages Di Bursa Efek Indonesia (BEI) Periode 2007-2011 - Muhammad Luthfi; Mulyani Mulyani; Eka Sari Ningsih (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2014)
The aimed of this study was to examine the influence of company size, profitability, operating leverage and net profit margin. The factors being examined are company size, profitability, operating leverage and net profit margin. Eckel index is used to determine the income smoothing practice. The study was involving 12 Food and Beverages Company that listed in Indonesian Stock Exchange, within a period between 2007-2011. The examination of hypothesis method using multivariate regression to examine the influence of company size, profitability, operating leverage and net profit margin toward income smoothing. The result of this study that company size, profitability, and net profit margin have significant effect to income smoothing. Operating leverage does not have significant effect to income smoothing.